Belas Kasihan yang Menggerakkan Pelayanan: Refleksi Eksegetis Matius 9:36 di Era Individualisme - Moranda Girsang; Luciana Haryanto (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to uncover the theological meaning of Jesus' compassion as expressed in Matthew 9:36 through a biblical exegetical approach. This verse demonstrates Jesus' emotional and spiritual response to the plight of the crowd, described as